Effects of selenium yeast and jujube powder dietary supplements on conformational and functional properties of post-mortem chicken myofibrillar protein - Wang, Zhuo; Yang, Chao; Tang, Defu; Yang, Xue; Zhang, Li; Yu, Qunli (Frontiers in Nutrition, 2022)
The aim of the study was to evaluate the effects of selenium yeast and jujube powder on the structure and functional properties of post-mortem myofibrillar protein (MP) in white feather broilers. Changes in the structure (surface hydrophobicity, secondary and tertiary structure), functional properties (solubility, turbidity, emulsifying, and foaming characteristics), and gel properties (gel strength, springiness, and water holding capacity) of the MPs of white feather broiler, which were fed with different concentrations of selenium yeast or/and jujube powder (selenium yeast: 0,0.3, and 0.6 mg/kg; jujube powder: 8% to replace corn) for 42 days, were determined at 0, 24, and 72 h post-mortem. The results showed that with increasing concentrations of selenium yeast and jujube powder in the diet, the α-helix content, solubility, emulsification, and foaming of post-mortem chicken MP increased significantly (P<0.05). The gel strength, springiness, and water holding capacity of MP also increased, but the differences between the treatment groups were not significant (P>0.05). In addition, the β-folding content and turbidity of MP decreased significantly (P<0.05). Both the increase in selenium yeast levels and the addition of jujube powder improved the structural integrity and functional properties of MP. The best improvement effect was found in the combination group of high-dose selenium yeast and jujube powder, and there were significant interactions between them in the indices of α-helix, β-folding, turbidity, emulsification, and foam stability of MP. In conclusion, supplementing diets with selenium yeast and jujube powder could maintain the structural stability of MPs in post-mortem chicken breast, leading to good functional properties. The results of this study may provide new insights into the effects of pre-slaughter feeding on post-mortem muscle MP conformation control and quality improvement.